Gastroblastoma in a 5-year-old child: a case report and literature review - Feng, Jizhen; Ling, Chunxiang; Xue, Yingjie; Li, Jiamei (Frontiers in Oncology, 2023)
Background: Gastroblastoma is an extremely rare stomach tumor with a biphasic cell morphology of epithelioid and spindle cells. Due to the low incidence rate and the lack of specific clinical characteristics, it is easy to misdiagnosis. The detailed imaging analysis was also unavailable. At present, we reported a case of gastroblastoma, to analyse its clinic and imaging characteristics. In addition, we reviewed the imaging findings, current diagnosis, treatment and outcome of gastroblastoma.Case Presentation: A five years old girl was admitted to our hospital with upper abdominal pain and melena. Endoscopic examination showed a protuberant submucosal mass on the greater curvature of gastric body. Abdominal ultrasonography and an abdominal enhanced computer tomography further confirmed the mass. The patient was pathologically diagnosed with gastroblastoma after radical surgery in February 2021.We described a rare case of gastroblastoma and may provide a new perspective towards imaging diagnosis, treatment and outcome of this tumor. Gastroblastoma tends to occur in males, typically affects young people, has low malignant potential and low rate of recurrence and metastasis. Gastroblastoma usually arise in the gastric muscularis propria with hypoecogenic and submucosal characteristics in ultrasound examination, and significant enhancement in CT scan.Surgical resection and regular follow-up after surgery are the main management of the disease.Clinicians should strengthen the understanding of this rare tumor for early detection and treatment.